2015
DOI: 10.17352/2455-2968.000004
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction of the Difficulty of Laparoscopic Cholecystectomy

Abstract: Introduction: Preoperative complexity estimation helps deciding whether to proceed with a minimally invasive approach, perform an open procedure or make a referral to a more experienced surgeon. Laparoscopic cholecystectomy outcome is particularly affected by the presence and severity of inflammation, advancing age, male sex and greater BMI. Objective:The aim was to trace outcome of laparoscopic cholecystectomy with difficult situation. Patients and Methods:A total of 204 patients with difficult situation chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…When it was soaked by 50% this means that it contains about 25 ml of blood and if soaked; 100% this means that it contains 75 ml of blood. 20 Many researchers reported a significant reduction of intraoperative blood loss by the use of suture less techniques in total thyroidectomy when compared with the conventional suture ligation technique and study data came in agreement with those reported results. [21][22][23] Al Juraibi et al also reported that the amount of intraoperative blood loss was 50-75 ml in sutureless group (mean 62.06±7.34) and 60-90 in the conventional group (mean 75.84±9.21).…”
Section: Discussionsupporting
confidence: 76%
“…When it was soaked by 50% this means that it contains about 25 ml of blood and if soaked; 100% this means that it contains 75 ml of blood. 20 Many researchers reported a significant reduction of intraoperative blood loss by the use of suture less techniques in total thyroidectomy when compared with the conventional suture ligation technique and study data came in agreement with those reported results. [21][22][23] Al Juraibi et al also reported that the amount of intraoperative blood loss was 50-75 ml in sutureless group (mean 62.06±7.34) and 60-90 in the conventional group (mean 75.84±9.21).…”
Section: Discussionsupporting
confidence: 76%
“…In a study of 204 patients with difficult situation cholecystitis in 2015, so the conversion rate was slightly high (7.35%). 8 Almost all LC are done in elective basis in our hospital. This might be the reason for slightly lower rate of conversion to open cholecystectomy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It was 3mm [12][13][14] or 4mm. 8 Critical gall bladder wall thickness was taken as 4mm in our study. Thickened gall bladder wall was found in 15 patients and was a significant predictor for difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeon-specific parameters were not included, observed or considered in this study. Some of these parameters were recognized in the literature as indicators of difficulty [15, [18][19][20][21]. Saber and coworkers estimated the difficulty of LC in a group of patients only with acute cholecystitis, but did not propose a prediction model [21].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these parameters were recognized in the literature as indicators of difficulty [15, [18][19][20][21]. Saber and coworkers estimated the difficulty of LC in a group of patients only with acute cholecystitis, but did not propose a prediction model [21]. Surge and coworkers offered a scoring system based on operative findings and the degree of cholecystitis in order to outline key operative findings [22].…”
Section: Discussionmentioning
confidence: 99%